Population pharmacokinetics of ofatumumab in patients with chronic lymphocytic leukemia, follicular lymphoma, and rheumatoid arthritis. (28th January 2014) - Struemper, Herbert; Sale, Mark; Patel, Bela R.; Østergaard, Mikkel; Österborg, Anders; Wierda, William G.; Hagenbeek, Anton; Coiffier, Bertrand; Jewell, Roxanne C.
Abstract Ofatumumab is a human monoclonal antibody directed at CD20 approved for treatment of chronic lymphocytic leukemia. The population pharmacokinetics of intravenous ofatumumab were characterized in patients with relapsed/refractory chronic lymphocytic leukemia, relapsed/refractory follicular lymphoma, and rheumatoid arthritis, diseases with widely varying CD20+ B‐cell counts in blood. Serum concentration data from a total of 477 patients who received ofatumumab doses ranging from 100 mg to 2000 mg in different dosing regimens were analyzed to determine the pharmacokinetic characteristics of ofatumumab across different patient groups and to identify factors contributing to the pharmacokinetic variability. Ofatumumab pharmacokinetics were well described by a linear two‐compartment model component to represent non‐specific monoclonal antibody clearance from the central compartment interacting with a model component representing the target‐mediated clearance of ofatumumab by binding to CD20 expressed on B cells. The clearance (7.5 mL/h) and steady‐state volume of distribution (5.3 L) for the linear, non‐specific component were consistent with results obtained for other monoclonal antibodies. The target‐mediated clearance component was related to the disease‐specific number of circulating B cells, which will allow simulation of the contribution of target‐mediated clearance to ofatumumab pharmacokinetics in untested disease states with data on B‐cell counts and turnover.